CANDIDATE GENES ASSOCIATED WITH POLYCYSTIC OVARY SYNDROME IN ASIAN POPULATIONS: A RESEARCH REVIEW - Vg, Abilash (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Polycystic ovary syndrome (PCOS) is a complex genetic condition and is a highly prevalent heterogeneous syndrome of clinical and biochemical androgen excess. The disease has genetic as well as environmental involvements. The normal menstrual cycle results from a coordination of hormonal secretion and signaling within the hypothalamic pituitary-ovarian axis. Alterations in the normal cycle or irregularity in menstrual cycle result in amenorrhea, abnormal uterine bleeding, etc. The main causes are PCOS, hormonal imbalance, drugs, nutritional deficiency, personality, some genetic factors, and many more. Women with PCOS are often resistant to the biological effects of insulin and, as a consequence, may have high insulin levels. Women with PCOS are at risk for type 2 diabetes, high cholesterol, and high blood pressure. Obesity also appears to worsen the condition. The impact of the syndrome on an individual varies significantly based on several factors such as the severity of the components, comorbidities, and life course considerations. In addition, each individual experiences the syndrome in the context of her own reproductive health, metabolic, and quality-of-life concerns. Hirsutism, obesity, and infertility are common complaints. This review article gives a detailed account on the association of candidate genes associated with PCOS in South Asian population. Keywords: Anti-mullerian hormone, Growth/differentiation factor 9, The bone morphogenetic protein, Follicle-stimulating hormone, Follistatin, Cytochrome p450, Polymerase chain reaction-restriction fragment length polymorphism.